Analisis Kepuasan Masyarakat Kota Medan terhadap Tim Gugus Tugas Covid-19 - Sri Rezeki; Diding Kusnady; Akhwanul Akmal; Indra Surya; Josi Farmiati; Supriyanto Supriyanto (Universitas Medan Area, 2020)
Indonesia one of the countries exposed by corona virus disease (Covid-19), so the government seriously form task force covid-19. Medan City is the provincial capital of North Sumatra have been exposed to corona virus disease (covid-19) until now starting on a sunday first in june had there are about 500 cases handled by the task force. Is an established by the provincial governments north sumatra to provide us with information in guarding the legal the spread of this virus . It be good or bad the performance of a cluster of a duty in perform this function or assessed by the community. One of the community assessment is a community satisfaction index. In determining community satisfaction index, used the quality and tangible service, responsiveness, reliability, assurance and emphaty. Dimensions tangible facilities team covering physical task force, equipment and personnel the task force. Dimensions responsiveness covering the readiness the task force in inform the community. The reliability covering the ability of the task force in providing services of information real and accurate. Dimensions assurance covering the ability of the task force knowledge related to the spread of covid-19. Dimensions emphaty covering an empathy team task force on the community of the City of Medan. Based on the research done, task force the Province of North Sumatra considered satisfied by the community of the City of Medan.